A review on oral malodor (halitosis) - Paricher Behfarnia; Narges Naghsh (Isfahan University of Medical Sciences, 2013)
Introduction: Oral malodor or halitosis has a prevalence of approximately 33%. In 90% of cases the causes of halitosis are located in the oral cavity. Diagnosis and treatment of oral malodor are primarily the responsibility of dentists.Review of Report: This is a review study in which electronic searches were run for halitosis in Pubmed and Medline from 1980 to 2012. Physiologic and pathologic halitosis, pseudo-halitosis (false halitosis) and halitophobia (fear from oral malodor) are discussed in this article. Pseudo-halitosis is a condition in which halitosis is non-existent but the patient is convinced that he or she has halitosis and if this idea persists after therapy for either genuine or pseudo-halitosis it is referred to as halitophobia. When the causes of halitosis are periodontal diseases or gingivitis, scraping of tongue is strongly advised in addition to conventional periodontal therapy and oral hygiene procedures. Diagnosis and treatment of halitosis with psychologic origin are more difficult than others and most patients receive unnecessary treatment.Conclusion: There are different treatment modalities for halitosis based on etiologic factors, which are presented in this article. It is important for the dentist to have a proper understanding of this prevalent oral condition and provide effective intervention and correct treatment.Key words: Diagnosis, Etiology, Halitosis, Oral hygiene